Chemical Heat Storage of Thermal Energy from a Nuclear Reactor by Using a Magnesium Hydroxide/Expanded Graphite Composite Material. (May 2015) - Zamengo, Massimiliano; Ryu, Junichi; Kato, Yukitaka
Abstract: In this work, chemical heat storage is proposed for the accumulation of the surplus thermal energy generated by a nuclear reactor during low demand of electricity and its re-utilization for the peak demands. Thermal energy is converted into chemical energy or vice versa by operating a reversible chemical reaction, consisting in the dehydration of magnesium hydroxide (Mg(OH)2 ) and the hydration of magnesium oxide (MgO). It is required that thermal energy has to be released promptly in order to follow the demand of electricity. To satisfy these features, the thermal conductivity of Mg(OH)2 and MgO has been enhanced by using expanded graphite (EG). A composite material, named EM, was obtained by mixing Mg(OH)2 and EG in a water suspension. After drying of the mixture, EM was compressed in figure of tablets (diameter of 10 mm, thickness of around 6 mm). The reactivity of the packed bed of EM tablets was and studied experimentally in order to determine its heat storage and heat output performances and compared to a packed bed made of pure Mg(OH)2 pellets. From the experimental results of stored heat and heat power output, it was possible to estimate the amounts of Mg(OH)2 and EM required for the peak shaving of electricity in a nuclear power station. A Rankine cycle in the power station has been modified to include a chemical heat storage reactor. The range of admissible variation of electrical power output from the steam turbine was estimated from the enthalpy and mass balances under the heat storage and heat output operation modes, respectively. The volume of EM tablets required to store the same amount of thermal energy of Mg(OH)2 pellets resulted 13.6% smaller.